Axiomatics of Fermat’s problem, another Way - Amelent A. E. (Science in figures, 2017)
the researcher of this article attempts to develop another Way to address the Fermat’s problem based on a different logical space, limited by other axioms, which have been described in the previous article of the author.
Keywords: «Арифметика» Диофанта; Ферма; диофантовые уравнения; теорема Ферма; «Arithmetic» of Diophantus; Fermat; Diophantine equations; Fermat's Last theorem